2020
DOI: 10.21203/rs.3.rs-38126/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust association between short-term ambient PM2.5 exposure and COVID prevalence in India

Abstract: Novel coronavirus (COVID) outbreak is the deadliest pandemic in our lifetime. The COVID prevalence risk may be enhanced due to comorbidity from other health risk factors like air pollution. However, such evidence is still lacking in India. Using daily confirmed cases, ambient PM2.5 (fine particulate matter) exposure and meteorological parameters from 28 major states of India between March 14-June 9, 2020, in a generalized additive model, we estimate the association between short-term PM2.5 exposure and daily C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Left alone, ambient, outdoor air pollution, causing an estimated 4.2 million deaths yearly worldwide [81], is a risk cofactor to be hypothesised in connection with a new respiratory disease, without necessarily having to analyse some of the other cofactors, especially in the temperate climate zones where new countries keep reporting similar correlations between PM 2.5 and the virus: the Netherlands [100,101], controlling for some other medical risk factors; Japan [102], finding a positive correlation in the elderly; and also India, which holds a similar trend in relation to the long-term hypothesis [103] and in relation to the short-term one, too [115,116]. Lastly, Canada [104], Peru [117], with other Latin America countries plus the Caribbean [118], and Malaysia [119] were reported to bear positive associations.…”
Section: Discussionmentioning
confidence: 99%
“…Left alone, ambient, outdoor air pollution, causing an estimated 4.2 million deaths yearly worldwide [81], is a risk cofactor to be hypothesised in connection with a new respiratory disease, without necessarily having to analyse some of the other cofactors, especially in the temperate climate zones where new countries keep reporting similar correlations between PM 2.5 and the virus: the Netherlands [100,101], controlling for some other medical risk factors; Japan [102], finding a positive correlation in the elderly; and also India, which holds a similar trend in relation to the long-term hypothesis [103] and in relation to the short-term one, too [115,116]. Lastly, Canada [104], Peru [117], with other Latin America countries plus the Caribbean [118], and Malaysia [119] were reported to bear positive associations.…”
Section: Discussionmentioning
confidence: 99%
“… Feldman et al (2021) India Increase in PM 2.5 exposure associated with increased COVID-19 incidence. Singh et al (2020) Malaysia COVID-19 cases were positively correlated with PM 10 , PM 2.5 , SO 2 , NO2, CO. Suhaimi et al (2020) Singapore • PM 2.5 , NO2 and pollutant standards index levels were positively associated with daily COVID-19 cases • PM 10 , O 3 , SO 2 , CO levels, rainfall and humidity were negatively associated with daily COVID-19 cases. Lorenzo et al (2021) …”
Section: Outdoor Airmentioning
confidence: 85%
“…Han et al have highlighted the association of PM 2.5 concentrations with the rate of a number of confirmed COVID cases in Wuhan, China. Further, Singh, Mhawish, et al ( 2020 ), Singh, Dey, et al ( 2020 ), Singh Singh, and Biswal ( 2020c ), Singh et al ( 2020d )) reported a significant linkage between short-term PM2.5 exposure and daily COVID-19-confirmed cases.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The adversity of exposure to air pollution is it can result in several kinds of cardio-pulmonary diseases and various types of cancers particularly in a vulnerable population of society which includes in particular infants and aged people (Ganguly et al, 2015 ; Prasad & Sanyal, 2016 ). In a recent study conducted by Singh, Mhawish et al ( 2020 ), Singh, Dey et al ( 2020 ), Singh Singh and Biswal ( 2020c ), Singh et al ( 2020d )) highlighted the effects of multiple air pollutants (BC, PM 2.5 , PM 10 , NO 2 ) on all-cause non-accidental mortality in Varanasi, a air pollution hotspot in Indo-Gangetic Plain. Samoli et al ( 2011 ) reported that a rise of 10 μg/m 3 PM 10 concentrations increased the cases of paediatric asthma by 2.54% in a study conducted in Athens, Greece.…”
Section: Introductionmentioning
confidence: 99%